2018
DOI: 10.56093/ijas.v88i10.84228
|View full text |Cite
|
Sign up to set email alerts
|

Bio-efficacy and post harvest residual toxicity of new fungicides against sheath blight (Rhizoctonia solani) of rice (Oryza sativa)

Abstract: Four new fungicidal formulations, viz. tebuconazole 50% + trifloxystrobin 25% WG, difenoconazole 25% SC, propiconazole 13.9% + difenconazole 13.9% EC and kresoxim methyl 44.3% SC were evaluated against Rhizoctonia solani Kuhn of rice (Oryza sativa L.) in vitro and under field conditions during kharif 2016 and 2017. In vitro growth inhibition tests revealed that the EC50 values of tebuconazole 50% + trifloxystrobin 25% WG, difenoconazole 25% SC, propiconazole 13.9% + difenconazole 13.9% EC and kresoxim methyl 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…These data were in accordance with Phelp and Soto [35] and Jones et al [36]. These finding are in full agreement with the previous reports of fungicide combinations such as azoxystrobin + difenconazole [19], kresoxim methyl + hexaconazole, fluxapyroxad + epixiconazole [31], trifloxystrobin + tebuconazole [37,32,38], flutolanil + azoxystrobin, thiophonate methyl + azoxystrobin, tebuconazole + azoxystrobin, propiconazole + azoxystrobin [39] reported the better efficacy against sheath blight.…”
Section: Sheath Blight Infectionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data were in accordance with Phelp and Soto [35] and Jones et al [36]. These finding are in full agreement with the previous reports of fungicide combinations such as azoxystrobin + difenconazole [19], kresoxim methyl + hexaconazole, fluxapyroxad + epixiconazole [31], trifloxystrobin + tebuconazole [37,32,38], flutolanil + azoxystrobin, thiophonate methyl + azoxystrobin, tebuconazole + azoxystrobin, propiconazole + azoxystrobin [39] reported the better efficacy against sheath blight.…”
Section: Sheath Blight Infectionsupporting
confidence: 93%
“…The combinatory chemical formulation such as Azoxystrobin 18.2% + Difenoconazole 11.4% [19,28], Trifloxystrobin 25% + Tebuconazole 50% [29,30], etc., are recommended to manage the disease. Recently, many combination fungicides such as kresoxim methyl 40% + hexaconazole 8%, azoxystrobin 18.2% + difenoconazole 11.4% SC, trifloxystrobin 25% + tebuconazole 50% 75 WG, have been shown to control the sheath blight disease under field condition [31,32]. It is vital to look for a novel molecule with a distinct mode of action because the constant use of fungicides belonging to the same group and having the same mode of action would cause the same fungi to evolve resistant strains.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural approaches, such as increased plant spacing, removal of agricultural residue, and the use of legume crops, can significantly reduce SB infection. Silica and soil amendments containing organic manures, such as neem cake, have also been shown to be effective against SB and to increase grain yield (Rodrigues et al, 2003;Kumar et al, 2006). Several reports have indicated that P. fluorescens strains exhibit systemic resistance to SB (Karthiba et al, 2014).…”
Section: Management Strategiesmentioning
confidence: 99%